(untitled) (Geneva, 1993)
This book introduce about recent trends on foreign direct investment. Direct employment in multinational enterprises in industrialized and developing countries in the 1980s...
Keywords: Doanh nghiệp kinh doanh quốc tế,International business enterprises; Quản lý,Management